Analisis Sistem Informasi Panda (SIP) Terhadap Penerimaan PenggunaMenggunakan Metode UTAUT - Evadila Shafira Salsabilla; Darmansah Darmansah; Dwi Januarita (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
PT. Puskomedia Indonesia Kreatif built a Village Information System named "Panda". PT. Puskomedia Indonesia Kreatif developed the Panda Information System with the hope that it would make it easier for village officials to get information with data owned by the village. The problem with the Panda Information System is that there has been no training on how to use the panda information system and there is no manual so that villages are less interested in using the application. The purpose of this study is to find out what factors influence the behavior of Panda Information System users. This study uses the UTAUT (Unified Theory of Acceptance and Use of Technology) method and uses the variables of Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Condition, Behavioral Intention and Use Behavior. The software used is SPSS 25 and SmartPLS. The analytical method used is descriptive analysis and SEM analysis. Results Based on the research, it was found that the pValues of the Behavioral Intention variable on Use Behavior was 0.142 > 0.05, variable Effort Expectancy on Behavioral Intention is 0.179 > 0.05, variable Facilitating Conditions on Use Behavior is 0.346 > 0.05, variable Performance Expectancy on Behavioral Intention is 0.498 > 0.05, andvariable Social Influence on Behavioral Intention is 0.418 > 0.05 so it is considered insignificant.